Metagenomic analysis of core differential microbes between traditional starter and Round-Koji-mechanical starter of Chi-flavor Baijiu - Liang, Jinglong; Deng, Lichuan; Li, Zhipu; Fei, Yongtao; Bai, Weidong; Zhao, Wenhong; He, Songgui; Cao, Rongbing (Frontiers in Microbiology, 2024)
Xiaoqu starter serves as the saccharifying and fermenting agent in the production of Cantonese soybean-flavor (Chi-flavor) Baijiu, and the complex microbial communities determine the flavor and quality of the product. Round-Koji-mechanical starter (produced by using an automated startermaking disk machine) is advantageous as it decreases operator influence, labor costs, and fermentation time, but the product quality is lower compared to traditional starter. Thus, two types of starters (traditional and Round-Koji-mechanical starter) from a Cantonese Baijiu factory were compared in a metagenomic analysis to investigate the differences in microbial community composition and core microbes. The results showed that several core microbes related to carbohydrate metabolism, amino acid metabolism and lipid metabolism, were differentially enriched in the traditional starter. Mucor lusitanicus and Rhizopus delemar were significantly positively correlated with the three key metabolic pathways. Saccharomyces cerevisiae, Cyberlindnera fabianii, Kluyveromyces marxianus, Lactobacillus fermentum, Mucor ambiguous, Rhizopus microspores, Rhizopus azygosporus, Mucor circinelloides, and Ascoidea rubescens were significantly positively correlated with two of the three key metabolic pathways. The results of this study provide a basis for understanding the differential core microbes in traditional and Round-Koji-mechanical starters of Chi-flavor Baijiu, and they also provide guidance for improving Round-Koji-mechanical starter.